X‐linked markers in the Duchenne muscular dystrophy gene associated with oral clefts. (13th March 2013) - Patel, Poorav J.; Beaty, Terri H.; Ruczinski, Ingo; Murray, Jeffrey C.; Marazita, Mary L.; Munger, Ronald G.; Hetmanski, Jacqueline B.; Wu, Tao; Murray, Tanda; Rose, Margaret; Redett, Richard J.; Jin, Sheng C.; et al.
<x xml:space="preserve">Abstract</x> As part of an international consortium, case–parent trios were collected for a genome‐wide association study of isolated, non‐syndromic oral clefts, including cleft lip (CL), cleft palate (CP), and cleft lip and palate (CLP). Non‐syndromic oral clefts have a complex and heterogeneous etiology. Risk is influenced by genes and environmental factors, and differs markedly by gender. Family‐based association tests (FBAT) were used on 14, 486 single nucleotide polymorphisms (SNPs) spanning the X chromosome, stratified by type of cleft and racial group. Significant results, even after multiple‐comparisons correction, were obtained for the Duchenne muscular dystrophy (DMD) gene, the largest single gene in the human genome, among CL/P (i.e. both CL and CLP combined) trios. When stratified into groups of European and Asian ancestry, stronger signals were obtained for Asian subjects. Although conventional sliding‐window haplotype analysis showed no increase in significance, selected combinations of the 25 most significant SNPs in the DMD gene identified four SNPs together that attained genome‐wide significance among Asian CL/P trios, raising the possibility of interaction between distant SNPs within the DMD gene.